Illocutionary Act In Finding Dory Film - Febrimadani, Rendis; Arifin, M. Bahri; Setyowati, Ririn (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2023)
ABSTRACTThis study aims to find out the illocutionary acts uttered by the characters in the Finding Dory film based on Searle's theory and to identify the function of illocutionary acts uttered by the characters in the Finding Dory film based on Leech's theory. This study was conducted to further discuss how the characters convey the meaning from the utterances or dialogues. The utterances or dialogues convey the meaning that has a function that can turn speech into action. The forms of illocutionary acts represented by the characters in Finding Dory film were analyzed using the illocutionary acts by Searle's theory and also identified the function of illocutionary acts. This study was descriptive qualitative because the data were the utterances of the characters in the Finding Dory film. there were three-step that the researcher followed to complete this study. The first step is for the researcher selected the utterances or dialogues by three characters, which are Dory, Marlin, and Nemo in the Finding Dory film that contains illocutionary acts and categorized them; then the researcher identified the function. The second step is the researcher presented the findings by using the descriptive method. The last step is for the researcher to conclude from the findings. In this research, the researcher reveals that a good conversation can be called successful if each character can understand the meaning of the utterances conveyed by each other. In the Finding Dory film, the researcher found three types of illocutionary acts; they are assertive, directive, and expressive, and thus, the three types of functions of illocutionary acts; are collaborative, competitive, and convivial by the character’s utterances or dialogues. Keywords: Illocutionary Acts, Functions of Illocutionary Acts, The Finding Dory film ABSTRAKPenelitian ini bertujuan untuk mengetahui tindak ilokusi yang terdapat dalam tuturan para tokoh dalam film Finding Dory yang dilandasi oleh teori Searle dan untuk mengidentifikasi fungsi tindak ilokusi tuturan para tokoh dalam film Finding Dory yang dilandasi oleh teori Leech. Penelitian ini dilakukan untuk membahas lebih jauh bagaimana para tokoh menyampaikan makna melalui tuturan atau dialog.Tuturan atau dialog yang disampaikan mengandung makna yang memiliki fungsi yang dapat mengubah tuturan menjadi suatu tindakan. Bentuk-bentuk tindak ilokusi yang diwakili oleh para tokoh dalam film Finding Dory dianalisis dengan menggunakan teori tindak ilokusi Searle dan juga mengidentifikasi fungsi tindak ilokusi. Penelitian ini bersifat deskriptif kualitatif Karenadatanya berupa tuturan-tuturan para tokoh dalam film Finding Dory. Ada tiga langkah yang peneliti lakukan untuk menyelesaikan penelitian ini. Langkah pertama peneliti memilih dialog ujaran dari tiga karakter, yaitu Dory, Marlin, dan Nemo dalam film Finding Dory yang termasuk tindak ilokusi dan mengkategorikannya; kemudian peneliti mengidentifikasi fungsinya. Langkah kedua, peneliti mempresentasikan temuannya dengan menggunakan metode deskriptif. Langkah terakhir adalah peneliti menarik kesimpulan dari temuan. Dalam penelitian ini, peneliti mengidentifikasi bahwa percakapan yang baik dapat dikatakan berhasil jika masing-masing karakter dapat memahami makna dari tuturan yang disampaikan oleh satu sama lain dalam film Finding Dory, peneliti menemukan tiga jenis tindak ilokusi, yaitu asertif, direktif, dan ekspresif, dan tiga jenis fungsi tindak ilokusi, yaitu kolaborasi, kompetitif, dan convivial berdasarkan tuturan atau dialog para tokoh. Kata Kunci: Tindak Ilokusi, Fungsi Tindak Ilokusi, film Finding Dory